نحو مؤشر إلزامي للإفصاح المحاسبي البيئي - د. داليا على محمد منصور (Aljameai, 1970)
Abstract:It is necessary the  availability of certain standards and indicators to deal with environmental  information as well as to explain how disclose it whether in the financial statements or separate environmental reports. The objective of this research is  trying to find out the index for the disclosure of environmental information, , and that guided by issues of international standards issued by professional organizations as well as the laws and legislation, as well as consulting with experience in this area of ​​accountants of Libyan audit bureau , private audit offices additionally environmentally sensitive companies of accountants at financial departments in the Libyan oil sector and finally commercial banks. It  have been used  descriptive statistics in order to reach the most acceptable standards by these parties.